Everyday environmental toxins : children's exposure risks (CRC Press, 2015)
This collection of timely chapters presents a nuanced study of environmental toxins and the risks they pose to children's development. The book details the impact of a number of commonplace environmental toxins, focusing on everyday exposure to tobacco smoke, lead, pesticides, and flame retardants. There is growing recognition that the impact of the environment on children's health is of critical importance for both current and future generations. In the last half-century, thousands of chemicals have been introduced into the environment with limited-although growing-research on the consequence.